The Use of a CAD/CAM Thermoformed Splints System in Closed Reduction of Condylar Fractures - Cristina Grippaudo; Antonino Lo Giudice; Gianmarco Saponaro; Mattia Todaro; Alessandro Moro; Antonio D’Addona (Bioengineering, 2023)
(1) Background: Mandibular fractures are very common. Common indications of closed treatment for mandibular fractures are non-displaced or minimally displaced simple fractures in adult compliant patients with good dentition, the absence of occlusal disruption, and fractures in growing children. In closed treatment, the mandible is maintained in centric occlusion with a maxillomandibular fixation (MMF) with orthodontic elastics. Many methods of MMF have been described, often using orthodontic appliances. In recent years, CAD-CAM technology has improved many procedures used in maxillofacial surgery and orthodontics. The device we present is manufactured following a digital workflow, and was designed specifically for MMF. (2) Materials: Two patients with mandibular fractures were treated with an MMF method whose procedure comprised scanning of the dental arches, followed by construction of thermoformed splints on which buttons for the elastics and retention holes are made. The splints were fixed on the dental arches with composite resin at the level of the holes, and were kept in place for the period of healing of the fracture, with the intermaxillary elastics hooked to the buttons. (3) Results: The application time of the splints was very quick. The splints remained stable for the necessary time, without causing particular discomfort to the patients. (4) Conclusions: From our experience, this technique has proved to be reliable and reproducible and could represent a valid tool in the closed treatment of mandibular fractures.